Application of Modular Vertical Gardening Racks to Improve Vegetable Cultivation Skills among Urban Communities - Novan Habiburrahman; Novie Priyanti; Aulia Rahman; Putra Dwiantoko (⁠International Journal of Asia Pacific Community Service, 2026)
Limited household land is one of the main constraints on vegetable cultivation in densely populated urban areas. This community service program aimed to introduce modular vertical gardening racks and improve the knowledge and practical skills of urban communities in cultivating short-cycle leafy vegetables. The program was conducted with residents of RT 007/RW 01, Bandulan, Sukun District, Malang City, in February 2026 and involved 30 participants. The activities consisted of a partner needs assessment, participatory rack fabrication, training in plant biology and cultivation techniques, installation, and four weeks of mentoring. The racks were designed using hollow-steel frames with bolted joints, three planting levels, and removable planting containers, allowing them to be easily assembled, relocated, maintained, and expanded according to the available space. Program outcomes were evaluated using pretest and posttest questionnaires, skill observation sheets, participant response questionnaires, and plant growth monitoring. The program produced eight modular vertical gardening racks equipped with 72 planting containers. The participants’ mean knowledge score increased from 56.3 on the pretest to 84.7 on the posttest. Furthermore, 86.7% of the participants achieved the competent category in rack assembly and vegetable cultivation. At the end of the monitoring period, the plant survival rate reached 93.1%, supported by appropriate growing-medium preparation, watering practices, and light management. The program demonstrates that an interdisciplinary approach integrating manufacturing engineering and plant biology can provide practical, affordable, and replicable urban agriculture technology. Continuous mentoring and evaluation over several planting cycles are recommended to strengthen community independence and ensure program sustainability.